2019
DOI: 10.1159/000500668
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Nondialysis Chronic Kidney Disease: Correlates and Association with Kidney Outcomes

Abstract: Background: Fatigue, although common and associated with outcomes in dialysis-dependent chronic kidney disease (CKD), has not been studied in nondialysis chronic kidney disease (CKD-ND) patients. Methods: In this longitudinal cohort of 266 outpatients with CKD-ND stages 2–5, we measured self-reported fatigue on 3 scales-Quick Inventory of Depression Symptomatology-Self Report (QIDS-SR16), Beck Depression Inventory-I (BDI-I), and short form 12 health survey (SF-12) questionnaires and evaluated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…These findings support that inflammation may be an important mediator or confounder of the associations of depression and fatigue with long-term death, hospitalization, and dialysis initiation that our group previously reported among patients with non-dialysis CKD. 2,3,35 Notably, the correlation we observed between higher levels of baseline plasma hsCRP and depressive symptoms was primarily driven by the burden of somatic symptoms, with ESKD that found baseline associations between inflammation and depression but no longitudinal changes in inflammatory biomarkers, as observed in our analysis. 36 In our study, although baseline hsCRP was higher in those with a favorable sertraline response, there was no change in hsCRP or other inflammatory biomarkers from baseline to study exit in those treated with sertraline, regardless of change in depressive symptoms.…”
Section: Discussionsupporting
confidence: 50%
“…These findings support that inflammation may be an important mediator or confounder of the associations of depression and fatigue with long-term death, hospitalization, and dialysis initiation that our group previously reported among patients with non-dialysis CKD. 2,3,35 Notably, the correlation we observed between higher levels of baseline plasma hsCRP and depressive symptoms was primarily driven by the burden of somatic symptoms, with ESKD that found baseline associations between inflammation and depression but no longitudinal changes in inflammatory biomarkers, as observed in our analysis. 36 In our study, although baseline hsCRP was higher in those with a favorable sertraline response, there was no change in hsCRP or other inflammatory biomarkers from baseline to study exit in those treated with sertraline, regardless of change in depressive symptoms.…”
Section: Discussionsupporting
confidence: 50%
“…Another element described in this category was the level of exhaustion the patients felt. Fatigue is often a major problem in patients with a kidney disease, and is seen in 60-97% of patients with ESKD undergoing hemodialysis, and as many of 69% of non-dialysis patients with CKD [20]. It has been reported to be a major obstacle to maintain usual daily activities and quality of life [21].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD are known to experience profound fatigue and it is one of the most common symptoms affecting their HRQoL [ 43 , 44 ]. One study reported how fatigue was associated with unemployment, comorbidities, and use of antidepressant medication; the authors suggested that the presence of fatigue may act as a clinical prognostic factor in CKD [ 45 ]. Patients experiencing sleep disorders and fatigue are also at increased risk of all-cause mortality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of fatigue experienced by this subset of PLM patients is likely to be multifactorial [ 41 ] and associated with prevalent complications such as anemia [ 41 , 45 ] and low albumin levels [ 42 ], psychosocial factors including depression and anxiety [ 41 ], and insomnia [ 46 ]. Improved understanding of the impact that fatigue and other symptoms such as depression and anxiety have on those living with CKD can help guide treatment and improve quality of care by prioritizing interventions that improve HRQoL, such as personalized care, precision medicine, or wearable technology and biometric devices.…”
Section: Discussionmentioning
confidence: 99%